2002
DOI: 10.4102/satnt.v21i4.239
|View full text |Cite
|
Sign up to set email alerts
|

Avifauna in grassland communities at some inland airports in South Africa.

Abstract: Over a period of eleven years (January 1985 – December 1995) approximately 5 000 individuals representing 51 bird species which, potentially, posed a threat to aviation were collected at the Bloemfontein airport. More than half of the species concerned can be considered as medium sized terrestrial birds of which the crowned plover (Vanellus coronatus) is by far the most important. A similar species composition occurred at the Kimberley airport, in contrast to the greater percentage of water associated birds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This study confirmed some of the findings of Kok & Kok (2002) who found that the Grey-headed Gull constituted almost half of the total number of birds recorded at ORT. We found that Grey-headed Gulls made up about 60% of the birds recorded while the African Sacred Ibis accounted for about 32%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirmed some of the findings of Kok & Kok (2002) who found that the Grey-headed Gull constituted almost half of the total number of birds recorded at ORT. We found that Grey-headed Gulls made up about 60% of the birds recorded while the African Sacred Ibis accounted for about 32%.…”
Section: Discussionsupporting
confidence: 91%
“…Grey-headed Gulls were indeed involved in the majority of collisions where species could be identified (Table 3; 14.2%). However, even though airports can be considered to be grasslands (Froneman, 2000;Kok & Kok, 2002;Mundy, 2003) and should therefore mostly attract grassland birds, the habitats surrounding the airport also influence the diversity and abundance of bird species flying through the airspace (Mundy, 2003; ICAO (International Civil Aviation Organization), 2010). Of all the collisions reported, 33% can be directly ascribed to water birds (calculated from Table 3), indicating that both terrestrial and aquatic bird habitats would require intervention.…”
Section: Discussionmentioning
confidence: 99%